Spillover Effects of Specialization Strategies in Hospitals: An Analysis of the Effects in the Short, Medium, and Long Term - Carsten Bauer; Nele Möbs; Oliver Unger; Andrea Szczesny; Christian Ernst (ZBW – Leibniz Information Centre for Economics, 2020)
In most developed countries, the economic pressure on hospitals to improve their efficiency has increased considerably over the past 30 years. Simple cost reimbursement for hospital care has almost universally been superseded by much more high-powered economic incentive-based systems. These systems offer powerful incentives to reduce expenses, particularly in high-cost areas such as the operating room (OR). Specialization is one prominent response strategy to such pressures. Whether these cost-saving strategies affect later events in the patient's case or the overall costs of a case has not been investigated yet. This study tries to answer the question of whether cost-reduction efforts by specialization in the OR deploy spillover effects on non-specialized cases. If they do so, the study tries to evaluate these spillover effects on a larger scale that considers the entire patient's case, since the cost-reduction efforts may actually be counterproductive because of adverse effects in the medium to long term.
Keywords: I11; M41; 330; cost pressure; specialization; learning effects; spillover effects; follow-up costs